Evapotranspiration From Developed Land and Urban Watersheds in a Humid Subtropical Climate - Jeremy E. Diem; Dinah K. Carlton; Luke A. Pangle (Water Resources Research)
Abstract Urbanization introduces new and alters the existing hydrological processes. Projecting the direction and magnitude of change of evapotranspiration (ET), often a large existing process, in humid subtropical climates is difficult due to the lack of land‐cover specific estimates of ET. This research aims to improve our fundamental understanding of ET in urban areas by focusing on ET specific to land‐cover classes of the National Land Cover Database (NLCD). Using multiple physically based models along with ET from reference watersheds, this study estimates ET—within the Atlanta, GA, USA region—for NLCD classes. ET also is estimated for urban watersheds—both in the Atlanta region and in areas with humid subtropical climate types—for which published ET estimates exist. There are major differences in land cover among the four developed classes: high‐intensity developed land is 92% impervious surfaces, while open‐space developed land—the least intensively developed land—is only 8% impervious surfaces. Consequently, open‐space developed land has an ET total that is over four times that of high‐intensity developed land. Due to a high percentage of impervious cover and substantial evaporation of water from impervious surfaces throughout the year, there is little intra‐annual variation in ET for the high‐intensity developed class. The land‐cover ET totals aggregate to reliable estimates for urban watersheds. The largest source of uncertainty for ET estimates in urban areas is likely the evaporation magnitude associated with impervious surfaces; therefore, more work is needed in determining those magnitudes for humid subtropical climates.